Evaluation of the Visual Environment of Community Third Places Based on Emotional Perceptions - Changchun Liu; Shupan Chen; Yumeng Jin (Buildings, 2025)
A well-designed visual environment in community third places has significant positive effects on residents’ emotional well-being. Only a few studies have examined these effects; therefore, this study comprehensively explores the effect of the visual environment on emotions through perception evaluations and physio-logical feedback data in a community café. The results show that light color temperature, light illuminance, spatial scale, interface decoration, illumination mode, and table and chair layout have significant effects on perception evaluation, while physiological feedback is significantly affected by light illuminance, spatial scale, illumination mode, and indoor plants. Neutral or warm light color temperatures, moderate or larger spatial scales, more interface decorations, and arranged table and chair layouts can significantly enhance positive emotions such as joy and optimism. Larger or smaller spatial scales, mixed or natural illumination modes, and fewer indoor plants significantly improve the fixation count and saccade count. In addition, there is a weak correlation between perception evaluation of emotions and physiological feedback. The findings of this study provide a scientific basis for improving the visual environment of the community third places and promoting the emotional recovery of residents.